1986
DOI: 10.2307/2045708
|View full text |Cite
|
Sign up to set email alerts
|

Property C, Refinable Maps and Dimension Raising Maps

Abstract: Abstract. We show that refinable maps defined on compacta preserve Property C. H. Kato has proved the analogous result for weakly infinite dimensional spaces. We also show that if / is a map from a compact C space X onto a non C space Y, then the set of points in Y with an uncountable number of preimages is a space that does not have Property C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Garity, Hattori, Rohm, and Yamada (see [4,5,6,18,19]) have shown that in the presence of tr-compactness the products of spaces with property C behave in a regular way. Our examples, based on totally imperfect sets, lack compactness-like properties.…”
Section: Introductionmentioning
confidence: 99%
“…Garity, Hattori, Rohm, and Yamada (see [4,5,6,18,19]) have shown that in the presence of tr-compactness the products of spaces with property C behave in a regular way. Our examples, based on totally imperfect sets, lack compactness-like properties.…”
Section: Introductionmentioning
confidence: 99%